Synthesis of metal-azo dyes and their optical and thermal properties as recording materials for DVD-R - Park, H; Kim, ER; Kim, DJ; Lee, H (CHEMICAL SOC JAPAN, 2002)
Four kinds of azo dyes and their metal-azo dyes were synthesized in order to obtain a high reflective index and better thermal stability as a recording material for DVD-R. Several kinds of novel azo dyes based on benzoic acid, 6-methoxybenzothiazole, benzothiazole-6-carboxylic acid, and benzimidazole have been synthesized. These azo dyes reacted with metal ions, such as Ni2+ Cu2+, Zn-2+, and Co2+, as ligands. All structures of the compounds were confirmed by H-1-NMR and FT-IR analyses. The optical and thermal properties of azo dyes and their metal-azo dyes were characterized by UV-vis and TGA analyses. In the UV-vis spectra, the absorption maxima of metal-azo dyes show at longer wavelength than those of azo dyes. These spectral shifts are affected by substituent groups, electron-donating or -withdrawing groups, of azo dyes and metal ions. The metal-azo dyes were thermally stable up to 300 degreesC, which were confirmed by TGA analyses. Particularly, in the case of an azo dye complexed with Zn based on 6-methoxybenzothiazole, good absorption at 635 nm was observed, and its thermal stability was maintained up to 300 degreesC, with high refractive index of about 2.08.
Keywords: DISC-RECORDABLE DISCS; CRYSTAL; COMPLEXES